2016
DOI: 10.1055/s-0036-1582604
|View full text |Cite
|
Sign up to set email alerts
|

Compression Loading Induced Cellular Stress Response of Intervertebral Disc Cells in Organ Culture

Abstract: Introduction Mechanical stress is often associated to interverterbal disc (IVD) degeneration and the effect of mechanical loading on IVD has been studied and reviewed.1,2 Previously, expression of heat shock proteins, HSP70 and HSP27 has been found in pathological discs.3 However, there is no direct evidence on whether IVD cells respond to the mechanical loading by expression of HSPs. The objective of this study is to investigate the stress response of IVD cells during compressive loading in an organ culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was found that longer loading durations significantly upregulated the Hsp70 level and had little influence on the apoptosis ratio of the NP cells, which indicated a protective effect following mechanical stress 65 . In addition, this research team also used adult bovine caudal discs to construct an organ culture model and found that Hsp70 expression appeared to be upregulated immediately after loading and was decreased upon resting following a repeated loading cycle in NP cells but not in AF cells 66 . In addition, a hypoxic or hypertonic microenvironment showed dramatic effects on mitochondrial function in NP cells 21,33,53 , in which the levels and function of the mitochondrial chaperone Hsp70 presented a corresponding response 67,68 .…”
Section: Mitochondrial Dysfunction and Idd Pathogenesismentioning
confidence: 99%
“…It was found that longer loading durations significantly upregulated the Hsp70 level and had little influence on the apoptosis ratio of the NP cells, which indicated a protective effect following mechanical stress 65 . In addition, this research team also used adult bovine caudal discs to construct an organ culture model and found that Hsp70 expression appeared to be upregulated immediately after loading and was decreased upon resting following a repeated loading cycle in NP cells but not in AF cells 66 . In addition, a hypoxic or hypertonic microenvironment showed dramatic effects on mitochondrial function in NP cells 21,33,53 , in which the levels and function of the mitochondrial chaperone Hsp70 presented a corresponding response 67,68 .…”
Section: Mitochondrial Dysfunction and Idd Pathogenesismentioning
confidence: 99%
“…The KEGG enrichment results showed that magenta module genes were mainly involved in “Phospholipase D signaling pathway” and “Osteoclast differentiation”. In most cases, the intracellular activity of phospholipase D remains low, unless the cells were stimulated by cellular stress (Bruntz et al 2014 ; Shin et al 2001 ), and we presumed that phospholipase D and associated signaling pathway might be activated in response to various cellular stress in IDD, such as mechanical stress (Chooi et al 2017 ) and oxidative stress (Hou et al 2014 ). Osteoclast is a crucial player in remodeling, maintaining, and repairing of bone tissue (Jayakumar and Di Silvio 2010 ), and was found activated in IVD with Modic changes (normally occur near the degenerated IVD), which could also be partially attributed to mechanical stress (Rahme and Moussa 2008 ; Torkki et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%